A Networked Intelligent Elderly Care Model Based on Nursing Robots to Achieve Healthy Aging - Wenting Ji; Ruzhen Luo; Yumei Sun; Maiping Yang; Yueheng Liu; Hua Chen; Dongmei Lin; Ziyi Su; Guangming Tao; Diansheng Chen; Hongyu Sun (Research)
As global populations become increasingly aged, existing elderly care models are proving insufficient. The development and application of nursing robots have shown potential in addressing the challenges of elder care in aging societies. This perspective outlines current state and potential applications of nursing robots in promoting healthy aging. Given this background, a networked intelligent elderly care model for nursing robots, which integrates technologies such as big data, artificial intelligence, the Internet of Things, and nursing robotics, is proposed. This model would synergistically combine elderly health monitoring, capability assessment, and intelligent allocation functions to revolutionize global elderly care practices and promote healthy aging.